2007
DOI: 10.1371/journal.ppat.0030201
|View full text |Cite
|
Sign up to set email alerts
|

A Single Mutation in Chikungunya Virus Affects Vector Specificity and Epidemic Potential

Abstract: Chikungunya virus (CHIKV) is an emerging arbovirus associated with several recent large-scale epidemics. The 2005–2006 epidemic on Reunion island that resulted in approximately 266,000 human cases was associated with a strain of CHIKV with a mutation in the envelope protein gene (E1-A226V). To test the hypothesis that this mutation in the epidemic CHIKV (strain LR2006 OPY1) might influence fitness for different vector species, viral infectivity, dissemination, and transmission of CHIKV were compared in Aedes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
1,244
5
34

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,344 publications
(1,310 citation statements)
references
References 45 publications
27
1,244
5
34
Order By: Relevance
“…Prior to this, CHIKV was not known to cause death in humans, then was transformed from nearly harmless to deadly. In comparison to the east African strain, the virus from Reunion Island had a single mutation of A226V in the envelope E1 protein (Tsetsarkin et al, 2007). Detailed analyses showed that this single mutation influenced vector fitness and viral infectivity.…”
Section: Epidemiology and Diseasementioning
confidence: 98%
“…Prior to this, CHIKV was not known to cause death in humans, then was transformed from nearly harmless to deadly. In comparison to the east African strain, the virus from Reunion Island had a single mutation of A226V in the envelope E1 protein (Tsetsarkin et al, 2007). Detailed analyses showed that this single mutation influenced vector fitness and viral infectivity.…”
Section: Epidemiology and Diseasementioning
confidence: 98%
“…albopictus, thus originating the ECSA Indian Ocean lineage (IOL) genotype (124). The E1-226V variant was more efficiently transmitted by A. albopictus (137), with a roughly 40-fold more efficient initial infection of midgut epithelial cells. The selection of the E1-226V variant occurs at the initial infection of the midgut of A. albopictus, leading to a higher viral dissemination and transmission of the IOL genotype by this mosquito.…”
Section: Virusmentioning
confidence: 99%
“…albopictus, this mutation is limited to CHIKV ECSA strains, and other mutations in E1 and E2 have been found to block the A226V E1-mediated adaptation to Ae. albopictus (137).…”
Section: Virusmentioning
confidence: 99%
“…A vigorous immune response limits the disease produced by CHIKV and confers protection from re-infection. Thus, the migration of monocyte/macrophages into the synovial tissues likely contributes to the infl ammation of joints and may explain the persistence of arthritis despite the lack of viremia 16 . In addition, the persistence of CHIKV in the joints of monkeys has been associated with chronic arthropathy.…”
Section: Chikungunya Virusmentioning
confidence: 99%